Relationship between anthropometric parameters and speed performance: A kinanthropometric research - Metin Can Kalaycı; Ferhat Guleroglu; Huseyin Eroglu (Türk Spor ve Egzersiz Dergisi)
The purpose in this study; determined of relationship between anthropometric parameters and speed performance. In this purpose; 118 sedentary university students age 21.2 ± 2.1 year, body weight 62.2 ± 10.7 kg and height 168.2 ± 8.1 cm participated in this study voluntarily. 30 m speed performance with stature (shoulder, chest, trunk, waist, hip, thigh, knee, calf and ankle) and (height, fathoms, upper arm, fore arm, all arms, trunk, thigh, leg and all leg) girths was measured. Statistical analysis was made in SPSS 22.0 packed program for Windows. Data from the measured of arithmetic means, standard deviation, lowest and highest values was found. Relationship between anthropometric parameters and speed performance was tested by Pearson's Correlation. According to Data from the measured; there were significant relationship in between speed values of workgroups and body weight, shoulder girths, chest girths, trunk girths, waist girths (p lt;0.01), leg girths (p lt;0.05) and there were significant relationship in between speed values of workgroup and height, fathoms length, fore arm length, all arm length, trunk length, leg length (p lt;0.01), thigh length (p lt;0.05). It can be said increases in speed values, if girths and length values increase.